Productivity Measurement Analysis Using Multi Factor Productivity Measurement Model (MFPMM) At PT. Primabox Adiperkasa - Much Syafiudin; Boy Isma Putra; Ribangun Bamban Jakaria; Tedjo Sukmono (Universitas Muhammadiyah Sidoarjo, 2022)
PT Primabox Adi Perkasa is a company located on Jl. Jaksa Agung Suprapto, Sumber Gedang, Pandaan, Pasuruan. This company is engaged in manufacturing, namely the production of cardboard boxes. This company can produce up to 550,000 pcs of cardboard boxes per year, employing 300 employees. The problem that arises in the company is caused by changes in the price of raw materials or materials which make changes in costs that must be considered in the production proces. Measuring productivity by using the Multi-Factor Productivity Measurement Model (MFPMM). This method is used to make it easier to measure changes in previous performance, controllers, and controllers of current company performance and can assess and evaluate the effect of profitability resulting from changes in productivity.The results of the research on Productivity Measurement Analysis Using the Multi-Factor Productivity Measurement Model (MFPMM) obtained the productivity index of used cardboard 89.69%, glue 97.72%, electricity 100.79%, fuel 82.24%, oil 109.61%, and The workforce is 123.75%.